2021
DOI: 10.3390/ijerph18083944
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Continuous and Interval Training under Hypoxia Enhances Endurance Exercise Performance with Hemodynamic and Autonomic Nervous System Function in Amateur Male Swimmers

Abstract: Hypoxic training is often performed by competitive swimmers to enhance their performance in normoxia. However, the beneficial effects of aerobic continuous and interval training under hypoxia on hemodynamic function, autonomic nervous system (ANS) function, and endurance exercise performance remain controversial. Here we investigated whether six weeks of aerobic continuous and interval training under hypoxia can improve hematological parameters, hemodynamic function, ANS function, and endurance exercise perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Interestingly, the combination of both continuous and intermittent training in a hypoxic condition has not shown significant enhancement in either aerobic or anaerobic performances. This type of combined hypoxia regimen can be divided into two as follows: 1) continuous and intermittent training sessions that are performed separately each week [ 22 , 88 , 89 ] and 2) continuous and intermittent training conducted during a session [ 21 , 23 , 90 , 91 ]. The result of comprehensive data indicates that engaging in additional continuous low-intensity training under hypoxia will not produce additional effects and may even deepen fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the combination of both continuous and intermittent training in a hypoxic condition has not shown significant enhancement in either aerobic or anaerobic performances. This type of combined hypoxia regimen can be divided into two as follows: 1) continuous and intermittent training sessions that are performed separately each week [ 22 , 88 , 89 ] and 2) continuous and intermittent training conducted during a session [ 21 , 23 , 90 , 91 ]. The result of comprehensive data indicates that engaging in additional continuous low-intensity training under hypoxia will not produce additional effects and may even deepen fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…According to the training duration and ratio of work to rest, intermittent training can be divided into repeated sprint training in hypoxia (RSH; work interval: 5–10 s and rest interval: approximately 30 s) [ 17 ], interval sprint training in hypoxia (ISH; work interval: 15–30 s) [ 18 ], high-intensity interval training (IHT; short duration: 1–2 min [ 19 ] and long duration: > 5 min [ 20 ]). In addition, some studies have combined continuous and intermittent hypoxia training aimed at optimizing aerobic and anaerobic capabilities concurrently [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated increased parasympathetic regulation of the heart after high-intensity exercise in correlation analysis results. Kim et al found an increase in ANS function in amateur male swimmers after 6 weeks of hypoxic high-intensity exercise ( Kim et al, 2021 ). High-intensity exercise may effectively alter cardiac function by activating beta-adrenergic receptors in the myocardium, improving the viability of the PNS and increasing venous return in a hypoxia environment ( Park et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the effectiveness of IHT may arise from its specific underlying mechanism or methodological design (Czuba, Fidos-Czuba et al, 2018). Unlike HH and HL, numerous studies have indicated that the hypoxic exposure of IHT is inadequate to substantially alter hematological parameters (Czuba et al, 2014;Czuba et al, 2019;Ambroży et al, 2020;Kim et al, 2021;Park et al, 2022;Teległów et al, 2022), and the potential mechanism for enhancing aerobic capacity primarily involves specific molecular adaptations in peripheral tissues (Ponsot et al, 2006;Zoll et al, 2006;Neya et al, 2007). It is worth noting that Czuba et al posited that a hematological mechanism is more effective in enhancing aerobic capacity (Czuba et al, 2018), and the diverse adaptations due to IHT contributes greatly to exercise (Green et al, 2000;Hamlin et al, 2010;Park et al, 2016;Saunders et al, 2004), which can also serve as a valuable metric for evaluating aerobic performance (Levine and Stray-Gundersen, 2005).…”
Section: Discussionmentioning
confidence: 99%